If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -18 = -47 Reorder the terms: -18 + m = -47 Solving -18 + m = -47 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + m = -47 + 18 Combine like terms: -18 + 18 = 0 0 + m = -47 + 18 m = -47 + 18 Combine like terms: -47 + 18 = -29 m = -29 Simplifying m = -29
| X+12+5y+7=180 | | 14(t-2)+7t=7(3t+4)-10 | | 2x+3y-4z-t=0 | | 14(t-2)+7t=(3t+4)-10 | | 4z^2-15z+9=0 | | 1000*101.3%= | | 1000+101.3%= | | (4z-5)(4-z)=0 | | 1000+1.3%*30= | | 1000+(1.3%*30)= | | 7n^2-55n-8=0factoring | | 2366716966=0.85*x | | 3p+8=12+2p | | 1250=0.85*x | | p-29=-46 | | 2p+5=9 | | 3q-5=4 | | 3y-3=3 | | 5-2y=3 | | (A+4)+3=12 | | 3(4x/7) | | 0.5x+20=0.3x+26 | | 3x^2-8=112 | | (N)5(7f-3)=28(f-1) | | 2f-2-6f+3=0 | | 1x+3y+4z=96 | | 7x^2+x= | | 500=-0.1x+1 | | x^6=-5x | | (x+21)+(x+9)=90 | | 3.6+(-4)= | | (H)3(y+1)=4y-21 |